Aberrant Brain Activity at Early Delay Stage Post-radiotherapy as a Biomarker for Predicting Neurocognitive Dysfunction Late-Delayed in Patients With Nasopharyngeal Carcinoma - Yang, Yadi; Lin, Xiaoshan; Li, Jing; Han, Lujun; Li, Zhipeng; Liu, Shiliang; Hou, Gangqiang; Xie, Chuanmiao; Lv, Xiaofei; Qiu, Yingwei (Frontiers in Neurology, 2019)
Background: Increasing evidence indicates that early radiation-induced subtle cerebral changes may be the precursors to permanent brain dysfunction at the late-delayed (LDS) post-radiotherapy (RT) stage. In this study, we aim to track the RT-related longitudinal brain activity in nasopharyngeal carcinoma (NPC) patients and to determine whether early abnormal brain activity can predict late neurocognitive dysfunction after RT. Methods: Thirty-three NPC patients were included and longitudinally followed up at the following time points: prior to treatment initiation, early-delayed stage (EDS, 1–3 months), and LDS (six months) after RT. Fifteen comparable healthy controls (HCs) were recruited and followed up in parallel. Montreal Cognitive Assessment (MoCA) was used to assess the general cognitive function. Brain activity was recorded via resting-state fMRI and regional homogeneity (ReHo). A whole-brain voxel-wise-based one-way repeated-measure analysis of variance (ANOVA) was conducted to evaluate the longitudinal ReHo changes among the three time points for NPC patients and HCs, respectively. Results were reported at the significant level of a threshold of two-tailed voxel-wise P< 0.01 and cluster level P< 0.05 with Gaussian Random Field (GRF) correction. Finally, the efficacies of the aberrant ReHo at EDS for predicting the cognitive impairment at LDS in NPC patients were evaluated. Results: Significant differences were detected in ReHo among the three time points in NPC patients but not in HCs. Aberrant ReHo was distributed in the bilateral cerebellum, the right temporal lobe, and the left insular areas, which showed different dynamic changes patterns over time. Logistic regression model combining the mean ReHo, age, and irradiation dose on the bilateral temporal lobe had the highest diagnostic efficiency according to the area under the curve (AUC) score (AUC = 0.752, P = 0.023). Conclusions: The post-RT brain activity revealed by ReHo in NPC patients was dynamic, complex, and multifactorial. Furthermore, the combination of the aberrant ReHo at EDS, age, and irradiation dose may serve as a potential biomarker of the RT-induced cognitive impairments at LDS.